2016
DOI: 10.1037/pri0000012
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and commitment therapy as a treatment for a Latina young adult woman with purging: A case report.

Abstract: Purging disorder (PD) is a new category of eating disorder, which is characterized by inappropriate compensatory behavior occurring in the absence of binging. There has been increasing evidence that acceptance and commitment therapy (ACT) may be an effective treatment for individuals with a range of maladaptive disordered eating concerns, including purging. The present case report shows therapeutic processes, course, and outcomes of a Latina woman with PD who participated in 10 weekly individual sessions of AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This occurrence may be influenced by the clinical condition of the illness suffered and the relatively short follow-up time. The implementation of ACT for patients with eating disorders showed a decrease in symptoms and improvement in body image at 3 and 12 months follow-up after ACT (Masuda et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This occurrence may be influenced by the clinical condition of the illness suffered and the relatively short follow-up time. The implementation of ACT for patients with eating disorders showed a decrease in symptoms and improvement in body image at 3 and 12 months follow-up after ACT (Masuda et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Research has shown clinical improvement in anxiety disorders after ACT during an 8-month follow-up (Codd, Twohig, Crosby, & Enno, 2011). ACT can also improve the response to body image of patients with eating disorders (Masuda, Ng, Moore, Felix, & Drake, 2016), lowering dissatisfaction with body image and attitude maladaptation after a 1 month followup (Walloch, 2015).…”
Section: Introductionmentioning
confidence: 99%